The Attitudes of Students and their Parents towards Vocational Education - Abd Rahman, Zakaria (1986)
This study aims to determine the attitudes of students and their parents towards vocational education. A sample of 120 students were selected from five schools in the district of Rembau, Negeri Sembilan, Malaysia. Three of the schools were vocational secondary schools and the remaining two were academic schools. The students and their respective parents were interviewed and their attitudes towards vocational education was measured using a Likert-type scale. Fifteen attitude statements pertaining to vocational education were posed to the subjects and their agreement or disagreement was recorded. It was found that the students and their parents had positive attitudes towards vocational education.